PENENTUAN RESIDU PESTISIDA PROFENOFOS GOLONGAN ORGANOPOSFAT PADA MENTIMUN DAN WORTEL DENGAN METODE GAS KROMATOGRAFI (GC) - Elizarni Elizarni; Afriana Afriana; Nanda Lutfhi Insani (Politeknik ATI Padang, 2018)
Horticultural commodities in the form of cucumbers and carrots are vegetables that are susceptible to pests and plant diseases. The use of pesticides is done to overcome the attack and quality of production. The use of pesticides in high doses and continuously will make a negative contribution in the form of contamination and accumulation of pesticide residues in agricultural products, pollution of the agricultural environment, decreased productivity, animal poisoning and poisoning in humans that are anti-health. The blood pesticide residue threshold is the Maximum Residue Limit (BMR) issued by the Minister of Agriculture Regulation Number 27 / Permentan / PP.340 / 5/2009, which is 0.5 mg / Kg. Detection of organoposfat profenofos pesticide residues was carried out to determine the level of food consumption in order to minimize the negative effects. The gas chromatography method is carried out to detect and analyze pesticide residues in cucumbers and carrots. The results showed that the levels of the active ingredient of pesticide organoposphate profenofos in cucumber 0.164 mg / kg and at wotel 0.2055 mg / kg. The content of pesticide residues in cucumbers and carrots based on the results of the study shows that the levels below the Maximum Residue Limit (BMR) have been determined.